Steel Structures Research Update:Seismic Performance and Design of Steel Panel Dampers for Steel Moment Frames - Liu, Judy (Engineering Journal, 2018)
Ongoing work on the seismic performance and design of steel panel dampers for steel moment frames is highlighted. Dr. Keh-Chyuan Tsai, professor in the Department of Civil Engineering at National Taiwan University, leads the team from National Taiwan University and the National Center for Research on Earthquake Engineering (NCREE) in Taipei. In 2018, At NCREE, one recent collaboration with the University of Washington included cyclic tests of a three-story chevron special concentrically braced frame (SCBF). Current seismic design provisions require large beam sizes to resist the unbalanced forces from the chevron braces after brace buckling. The research has explored options for alternative ductile mechanisms and reduced beam sizes. Steel research at NCREE has also included studies on steel beam-to-box-column moment connections and electro-slag-welded (ESW) joints in those connections. Meanwhile, research into premature fracture of ESW diaphragm-to-column joints in beam-to-box-column connections has revealed sensitivity to eccentricity in loading between the beam flange and the diaphragm. Further, a micromechanical-based stress-modified critical stress (SMCS) model has been developed and shown to be capable of predicting the crack initiation of the diaphragm-to-column ESW joint (Li et al., 2018).